Effect of different coating materials on freeze-drying encapsulation of bioactive compounds from fermented tea leaf wastewater - Kavinna Ravichai (2019)
© 2019 Wiley Periodicals, Inc. Bioactive compounds present in concentrated fermented Miang wastewater (CFMW) were encapsulated by freeze drying using various coating materials (maltodextrin, gum arabic, and modified starch) and CFMW-to-coating material ratios. The highest encapsulation efficiency of 98.05% was produced with gum arabic coating and 10:1 CFMW-to-coating ratio. The encapsulated Miang powder contained gallocatechin, epigallocatechin, catechin, epicatechin, gallic acid, and caffeine content of approximately 8.33, 27.81, 76.53, 8.01, 4.44, and 257.47 mg/100 g dry Miang powder (DMP), respectively. The antioxidant values (IC50) of the Miang powder were 22.44 µg/ml against DPPH radicals and 334.33 µg/mL against ABTS radicals. Similarly to the freeze-dried sample, spray-dried Miang powder formulated with gum arabic coating, which were prepared for comparison, achieved the encapsulation efficiency 85.18%, total catechins 105.22 mg/100 g DMP, DPPH IC50 value 21.88 µg/ml and ABTS IC50 value 366.32 µg/ml. Additionally, the encapsulated Miang powder could be utilized to enhance the value of low-quality tea drink. Practical applications: The wastewater from fermented tea leaf (Miang) production is an interesting natural source of phenolic compounds, including the antioxidants gallocatechin, epigallocatechin, catechin, epicatechin, and gallocatechin gallate. Freeze drying with gum arabic as a coating material can be utilized to encapsulate these bioactive compounds present in the wastewater of fermented Miang with high encapsulation efficiency. Encapsulated Miang powder could be used to enhance the value of low-quality tea drink. Therefore, encapsulated Miang powder is a natural bioactive compound source with the potential as an ingredient in food and beverage production.